2019
DOI: 10.1097/ans.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality and Critical Realism

Abstract: This article presents intersectionality theory with critical realism as a philosophical framework for studying nursing leadership. In response to gaps in the current leadership literature, the aim is to develop an approach that addresses how the multiple social positions nurses hold can create an intersecting matrix of oppression that impacts on their opportunities to develop as leaders. The result is a theoretical foundation, which can inform the methodological framework of future studies. Providing evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…In line with the reflections above, the results of the literature review show that there is a need for researchers to engage themselves with theoretical frameworks to address the issue of nurses' agency. The theoretical lenses of critical realism as used by Goodman ( 2017 ) and Williams et al ( 2016 ) have shown their value in highlighting the multiple ways in which agency is harnessed by nurses to confront forms of domination (Aspinall et al, 2019 , 2021 ; Schiller, 2016 ). However, critical theory lenses have been the ones that have made the most forceful contributions toward nurses' emancipation (Chulach & Gagnon, 2016 ; McMillan & Perron, 2020 , 2021 ; Paloniemi & Collin, 2012 ; Perron, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the reflections above, the results of the literature review show that there is a need for researchers to engage themselves with theoretical frameworks to address the issue of nurses' agency. The theoretical lenses of critical realism as used by Goodman ( 2017 ) and Williams et al ( 2016 ) have shown their value in highlighting the multiple ways in which agency is harnessed by nurses to confront forms of domination (Aspinall et al, 2019 , 2021 ; Schiller, 2016 ). However, critical theory lenses have been the ones that have made the most forceful contributions toward nurses' emancipation (Chulach & Gagnon, 2016 ; McMillan & Perron, 2020 , 2021 ; Paloniemi & Collin, 2012 ; Perron, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, intersectionality provides a foundation from which to examine the experiences of marginalized groups who navigate the various forms of oppression at their intersection and to examine processes of power and inequity. 29 Second, the intersectionality theory clarifies that individual and group inequities are shaped and informed by interactions between multiple levels of power, 30 such as institutional structures and discrimination structures as well as processes of marginalization, globalization, and neoliberalism. In other words, intersectionality shows that those with power maintain the status quo of inequity by making norms that are visible for examination in relation to the dominant culture, ethnicity, gender, and status.…”
Section: Why Critical Ethnography and Intersectionality In Research W...mentioning
confidence: 99%
“…In other words, intersectionality shows that those with power maintain the status quo of inequity by making norms that are visible for examination in relation to the dominant culture, ethnicity, gender, and status. 29 The third tenet of intersectionality is that examining only one aspect of a person's social location and identity will result in neglecting the simultaneous processes of the multiple experiences of oppression and marginalization that person may experience. 9,29,31 Therefore, each of the 2 approaches of critical ethnography and intersectionality has established strengths, and combining these approaches results in potential synergies.…”
Section: Why Critical Ethnography and Intersectionality In Research W...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we sought to illuminate the intersectionality of systemic and structural discrimination within our course activities to simultaneously support and strengthen student learning, while also addressing structural issues within nursing education that perpetuate discrimination. To elaborate, intersectionality is a lens through which one can analyze complex hierarchies and dominant ideologies that work together to create matrixes of power (Aspinall et al, 2019). As such, our focus in this discussion paper is to illuminate how we utilized anti-racist pedagogy to enact change in our educational practice.…”
Section: Introductionmentioning
confidence: 99%